What Would Jack Bauer Do? Negotiating Trauma, Vengeance and Justice in the Cultural Forum of Post-9/11 TV Drama, from 24 to Battlestar Galactica and Person of Interest - Tobias Steiner (European Journal of American Studies)
Discussing the concept of cultural trauma and its role in popular television dramas such as 24 (FOX 2001-10, 2014-), Battlestar Galactica (Syfy 2004-9), Rubicon (AMC 2010) and Person of Interest (CBS 2011-16), this paper sets out to identify three distinct clusters that are part of what Newcomb and Hirsch once termed a “cultural forum”—a discursive space in which questions of justice, revenge, terror, and trauma continue to be negotiated in significantly changing ways. Doing so, it finds that those clusters occur within a processual shift of cultural focus away from the early one-dimensional call for easy justice through retaliation motivated by the national narrative of heroes vs. perpetrators, towards a multifaceted occupation with the problems that U.S. society has been facing over the last seventeen years.